Powers and limitation of the molecular approach for the study of biogeography and speciation : examples in tropical African mammals - (:unkn) unknown (My University, 2002)
We attempted to test biogeographic hypotheses proposed for the evolution of tropical faunas using mitochondrial DNA sequences of selected African mammalian taxa (Insectivora, Rodentia and Primates). 1/ we constructed a molecular phylogeny of taxa in order to ascertain their monophyly and calibrate a molecular clock; 2/ we analysed and compared the phylogeographic patterns of five forest-dwelling taxa; 3/ we evaluated the evolutionary processes potentially involved in the speciation of cercopithecine Primates. Phylogenetic results confirm that gene history is not necessarily the same as organism history. Phylogeographic analyses reveal distinct patterns for each model species, suggesting differences in initial distributions or different responses to the same events. They indicate a role of Plio-Pleistocene vicariance events in the intra-specific diversification of small mammals. Thus, genetic divergence would be much older than the last glacial cycles. In cercopithecine Primates, speciation would have been predominantly allopatric and driven by Miocene and Pliocene vicariance events. Altogether, results give support to the refuge hypothesis, without excluding the riverine barrier nor the paleogrographic ones. They emphasize the role of paleo-ecological changes in generating diversity and of the main riverine barriers in shaping the present distribution of that diversity.
Keywords: African Research